An r-Hiding Revocable Group Signature Scheme: Group Signatures with the Property of Hiding the Number of Revoked Users - Keita Emura; Atsuko Miyaji; Kazumasa Omote (Journal of Applied Mathematics)
If there are many displaced workers in a company, then a person who goes for job hunting might not select this company. That is, the number of members who quit is quite negative information. Similarly, in revocable group signature schemes, if one knows (or guesses) the number of revoked users (say r), then one may guess the reason behind such circumstances, and it may lead to harmful rumors. However, no previous revocation procedure can achieve hiding r. In this paper, we propose the first revocable group signature scheme, where r is kept hidden, which we call r-hiding revocable group signature. To handle this property, we newly define the security notion called anonymity with respect to the revocation which guarantees the unlinkability of revoked users.